Geoprocessamento aplicado na caracterização da fragilidade ambiental da bacia hidrográfica do Arroio Grande, RS - Padilha, Damáris Gonçalves (2008)
The last decades have been marked by profound technological, social and economic changes, but above all, environmental, which have significantly affected the strategies of planning. One of the main tools used by public agencies in preparing the environmental territorial planning is the map of environmental fragility, because this kind of mapping allows to assess the potential of environments in an integrated way, matching its natural characteristics with its restrictions. In order to use geoprocessing technologies to identify areas of bigger and smaller environmental fragility of the Arroio Grande Watershed, it was used the methodology proposed by Ross (1994), with the aim to observe the real situation of the study environment, searching to promote the matching of the uses to their vocation features. The Arroio Grande River Basin is locating between the geographic coordinates 29º 29' 20" and 29º 43' 20" S and 53º 47' 30" and 53º 34' 20" W and has an area of 27,673.77 hectares. It s a medium to high fragility basin, especially as a function of the land use and occupancy as well as its terrain characteristics and soil units. The class of potential fragility with higher representativity is the mean fragility and occurs in an area of 12768.12 hectares, where dominate the Brazilian soil type Association (RRe1 Cxe TXp), with 57.27% of the soils belongs to this class and slope ranging from 12% to above 30%. The more representative class of emerging environmental fragility is called the average the mean fragility, present in 54.12% of total basin, presenting itself to 14977.87 hectares. The land use in the class presents the most forests, with 43.47%, followed by class field with 36.52%. Only 4.42% of the area gives strong fragility basin, of which 89.08% of the total understood by the class of exposed soil, and only 10.86% with the class of irrigated agriculture. Since there is a seasonality of agricultural production according to the region typical weather, during the period that the soil is not exposed the very strong emerging environmental fragility class declines, leading consequently increase of mean and strong fragility. Beyond the data produced in this study, other researches are needed to cover additional aims of environmental theme, because what matters is not an analysis of the isolated element but how the element interacts with the others, to be environmentally appropriate, economically viable and socially integrated.